The Guidance and counseling research trends in Indonesia: where does cybercounseling stand? - Prabawa, Abi Fa'izzarahman; Antika, Eni Rindi (KONSELOR, 2023)
Cyber counselling is a critical issue to be researched in the average era and implementation of the 21st century. This research aims to analyze the position of cyber counseling and its aftermath in the trend of guidance and counseling research in Indonesia.  Bibliometric analysis and content analysis were used to answer the research questions. The data sources were articles published in Indonesian journals accredited by Science and Technology Index (SINTA). The journals used to maintain the credibility of this research are journals with SINTA level 2 in the 2019-2022 period. Bibliometric analysis was processed with the help of the VOSviewer application. Content analysis was carried out through stages: 1) bringing together, 2) sampling, 3) recording/coding, 4) reducing, 5) inferring, and 6) narrating. The results showed that the issue of cyber counseling is an issue that still needs to be researched. Research on cybercounseling has an excellent opportunity to be explored by making variations and innovations in the aspects of researcher collaboration with multiple disciplines, research methods, subjects, research locations, data collection techniques, and data analysis.